Improving test efficiency through multiple criteria coverage based test case prioritization using modified heuristic algorithm - Joseph, A.K. (Institute of Electrical and Electronics Engineers Inc., 2016)
Test case prioritization involves reordering the test cases in an order that helps in attaining certain performance goals. The rate of fault detection is one of the prime goals that we tend to achieve while doing prioritization. Test cases should run in an order to increase the possibility of fault detection and it should be achieved early during the test life cycle. To reduce the cost and time of regression testing, test case prioritization should be done with the intention of periodically modifying the test suite. The humongous set of test cases makes it redundant and cumbersome for the testers who ensure quality for an end application. The fault detection capability of a prioritized test suite is improved up to 15 using Modified PSO which forms the base algorithms for prioritization. The algorithm illustrated detects serious errors at earlier phases of testing process and effectiveness between prioritized and unprioritized test cases. Â© 2016 IEEE.